Progestin-Primed Ovarian Stimulation Versus Mild Stimulation Protocol in Advanced Age Women With Diminished Ovarian Reserve Undergoing Their First In Vitro Fertilization Cycle: A Retrospective Cohort Study - Tu, Xiaoyu; You, Bingbing; Jing, Miaomiao; Lin, Chenxi; Zhang, Runju (Frontiers in Endocrinology, 2022)
Objective: To assess the feasibility of progestin-primed ovarian stimulation (PPOS) protocol for advanced age women with diminished ovarian reserve (DOR) undergoing their first in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) cycle by comparing it with mild stimulation protocol. Methods: Patients with ages of ≥35 years old and DOR undergoing their first IVF/ICSI cycle were enrolled in the retrospective cohort study:139 patients underwent PPOS protocol compared with 600 patients underwent mild stimulation protocol. The primary outcomes were cumulative clinical pregnancy rate (CCPR) and cumulative live birth rate (CLBR). The secondary outcomes were the number of oocytes retrieved and top-quality embryos. Results: There was nearly no significant difference of baseline characteristics between two groups. Although a greater amount of total gonadotropin (1906.61 ± 631.04 vs. 997.72 ± 705.73, P < 0.001) and longer duration of stimulation (9(10-7) vs. 6(8-4), P < 0.001) were showed in PPOS group, the number of retrieved oocytes (3(6-2) vs. 2(4-1), P < 0.001) and top-quality embryos (1(2-0) vs. 1(2-0), P = 0.038) was larger in PPOS group. Meanwhile, the incidence of premature luteinizing hormone (LH) surge rate was significantly lower in the PPOS group (0.7% vs.8.3%, P = 0.001). However, there was no significant difference in conservative CCPR, conservative CLBR, optimistic CCPR and optimistic CLBR between two groups (all P > 0.05). A multivariate logistic regression model showed that significant positive effects of the number of retrieved oocytes and number of top-quality embryos on conservative CCPR (OR=1.236, 95%CI:1.048-1.456, P = 0.012. OR=2.313, 95%CI:1.676-3.194, P < 0.001) and conservative CLBR (OR=1.250, 95%CI:1.036-1.508, P = 0.020. OR=2.634, 95%CI:1.799-3.857, P < 0.001) respectively, while significant negative effects of age were identified on the conservative CCPR (OR=0.805, 95%CI:0.739-0.877, P < 0.001) and conservative CLBR (OR=0.797, 95%CI:0.723-0.879, P < 0.001). Conclusion: the PPOS protocol is an effective alternative to the mild stimulation protocol for advanced age patients with DOR as it obtains comparable reproductive outcomes and better control of premature LH surge. Moreover, more oocytes and top-quality embryos were obtained in the PPOS group, which had a positive association with conservative CCPR and CLBR.